Hydrogeochemistry in a relatively unmodified subtropical catchment: Insights regarding the health and aesthetic risks of manganese - Adam K. Rose; Larelle Fabbro; Susan Kinnear (Journal of Hydrology: Regional Studies, 2017)
Study region: Metal and nutrient concentrations were analysed from freshwater and soil collected from a relatively unmodified ephemeral subtropical catchment in Central Queensland, Australia. Samples were collected quarterly between December 2012 and December 2014. Study focus: There is increasing concern about the health effects of manganese in drinking water, prompting interest in understanding manganese dynamics. This study investigated the temporal and spatial patterns of metals and nutrients, as influenced by summer rainfall; and the impacts of those variables on drinking water, associated infrastructure and concomitant health risks. New hydrological insights for region: Results show that the hydrogeochemistry of Baffle Creek was predominantly driven by rain events, with differing responses to varying magnitudes of rain and discharge. Following a flushing event, dissolved aluminium and nitrate increased in the surface and drinking water, whereas manganese and ammonia were undetectable in the drinking water and occurred only in small concentrations in the surface waters. In contrast, when rainfall events occurred without an associated flush, manganese, iron and ammonia concentrations increased in the drinking water. The hydrochemistry of manganese and iron in the supply chain infrastructure was strongly positively correlated with ammonia, and aluminium correlated with nitrate concentrations. Currently the drinking water supply does not pose a threat to chronic manganese exposure for humans, however elevated concentrations are experienced periodically; and may become more problematic under climate change scenarios.